Karakterisasi Metabolit Sekunder Bakteri Simbion Gastropoda Conus miles dengan Metode GC-MS Sebagai Antibakteri MDR (Multi Drug Resistant) - Hasanah, Nurul Fitrah; Pringgenies, Delianis; Wulandari, Sri Yulina (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
It is known that the bacterial symbionts are symbiotic with gastropods Conus miles has the potential to be able to produce antibacterial compounds against bacterial MDR (Multi Drug Resistant). Information found previously from bacterial symbionts and isolation based on screening results, the size of the zone of inhibition and inhibitory properties against several types of bacteria tests showed that isolates derived from Conus miles Gastropoda symbionts characterized by kinship rate of 98% in bacteria Pseudoalteromonas sp. The research objective was to determine the characteristics of the bacterial symbiont bioactive compounds associated with the type of mollusk Conus miles. The study was conducted three phases namely the isolation and purification of bacteria; characterization of isolates identified through test results on the reaction of physiological and biochemical tests, as well as the identification of secondary metabolites by GC-MS method QP2010S Shimadzu. The results showed that the bacterial symbiont isolates had a number of compounds with a percentage of the highest peak to the lowest compound the compound, Acetic acid (CAS) ethylic acid (35.22%); propanoic acid, 2-methyl-(CAS) Isobutyric acid (11.78%); Iso -valeric acid (9:38%), butanoic acid, 2-methyl-(CAS) 2-methylbutanoic acid (4.74%) and 1,2-Benzenedicarboxylic acid, dioctyl ester (CAS) Dioctyl phthala (4:36%). The results concluded that the bacterial symbiont isolates obtained in this study provide information on the results of potentially new antibiotics.